Pengendalian Plutella xylostella dan crocidolomia binotalis pada tanaman kobis dengan insektisida hayati - Joko Sumarmi, Sartono Joko Santoso & (Exsplorasi, 2008)
ABSTRACT A research carried out from July to October 2007 in Matesih village, Matesih district, Karanganyar regency at the evevation of 500 meters above seal levels. The aim of the research to study the effect of two kinds exstract of mimba seed and pipper seed to kill power P. xylostellaÂ  and C. binotalis of cabbage crop. The research method used Randomized Completely Block Design (RCBD) with 7 treamtmens and 3 replications, are : control, extract mimba seed 1%, 2%, 3%, and extract piper seed 1%, 2%, 3% concentration. The data were analysed using an Analysis of Variance and Duncans Multiple Range Test 5%. The treatment of extract mimba seed 2% and extract pipper seed 2% showed that best kill power to P.xyostella and C. binotalis the lowest damage intencity caused of extract mimba seed 3% and extract pipper seed 3%. The higgest weight of cabbage crop caused of extract pipper seed 3%. Key words : Botanical Insecticide, Cabbage Crop